Analysis of Spectrum Selection Methods Based on Platform-Qualnet in Cognitive Radio Networks - Sun, Hui; Han, Han (International Journal of Online and Biomedical Engineering (iJOE), 2019)
Dynamic spectrum Access ï¼ˆDSAï¼‰is used to make use of the spectrum in wireless network. In most situations, control channel is a common approach to negotiation between secondary users. But, based on this feature, the attacker can destroy the communication network only influence the control center. So, in this paper, two methods without control channel are simulated in Qualent platform. The results prove that those methods are available, and the Receiver-directed channel selection is more match to the regular control channel standards in throughput.